SKRINING FITOKIMIA JAMU YANG DIFERMENTASI DAN YANG TIDAK FERMENTASI - Ni Sri Yuliani; Gerson Y.I. Sakan; . Sirajudin (Partner, 2019)
Herbal medicine has been used an empirical prevention and treatment of diseases in livestocck. Herbal medicine contains several active compounds that can act as antimicobials, anthelmintics, antifungals, immunostimulant, and growth promoter. The herbs that are widely used are tuumeric, ginger, temulawak, and garlic as the basic ingredients of herbal medicine. Based on phytochemical screening test unfermented herbs containing positive Flavonoid compounds (+), negative Saponins (-), nagative Triterpenoids (-), Positive Alkaloids (+++), and positive tannins (+++). And fermented contains negative Flavonoids (-), positive Saponins (++), negative Triterpenoids (-), positive Alkaloids (+++), and negative tannins (-).